The Laws of the Médiéval Kingdom of Hungary. Décréta Regni Mediaevalis Hungariae. Vol. 1: 100- 1300. Translated and Edited by J. B. Back, G. Bónis, J. R. Sweeney with a critical essay on previous éditions by A. Czismadia. Ch. Schlacks, London 1989 - Russocki, Stanisław (Czasopismo Prawno-Historyczne, 1991)
Recenzja: The Laws of the Médiéval Kingdom of Hungary. Décréta Regni Mediaevalis Hungariae. Vol. 1: 100- 1300. Translated and Edited by J. B. Back, G. Bónis, J. R. Sweeney with a critical essay on previous éditions by A. Czismadia. Ch. Schlacks, London 1989